The Impact of Management Information Systems on Security Decision-Making : An Analytical Research for a Sample of Security Services Officers at Al-Muthana Governorate - Maraid Muhail*, Ahmed; Aftan Abdullah, Yousif (Journal of Economics and Administrative Sciences, 2024)
The current research aims to identify the extent of the impact of management information systems on the level of security decision-making among a sample of security services officers in Muthana Governorate, and the researcher used the descriptive analytical approach to present, analyze and then explain the information, and collect data through the questionnaire as a main tool, designed based on international standards after making amendments to its paragraphs consisting of (40) paragraphs that included the two research variables, as well as through the field coexistence of the researcher and personal interviews, and the questionnaire was distributed to all research community ( Comprehensive inventory) by (200) forms from officers working in the various directorates of security services in (Muthana Governorate) to retrieve (197) forms, valid for statistical analysis, including (191) form invalid for analysis (6) form, and non-retrieved (3) form, has been using a set of statistical methods and represented by the program (AmosV23 In some statistical aspects, the ready-made statistician (in a sample of security services officers in Muthana Governorate) in addition to the researcher's adoption of statistical methods (arithmetic averages, standard deviation, coefficient of differences, relative importance), the research has reached the most prominent result represented in: There is interest in improving the level of management information systems because of their role in making the finest security decisions in the directorates of the security services in Muthana Governorate.